Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar IPA Materi Ekosistem Menggunakan Model PBL DICONTOH (Problem Based Learning, Discovery Learning, Contextual Teaching and Learning, dan Number Head Together) pada Siswa Kelas V SDN Kuin Selatan 1 - Muniroh, Husnatul; Amberansyah, Amberansyah (CV. ITTC INDONESIA, 2024)
This classroom action research aims to improve critical thinking skills and learning outcomes in science, specifically on the topic of ecosystems, for fifth-grade students at SDN Kuin Selatan 1 Banjarmasin by using the PBL DICONTOH model (Problem-Based Learning, Discovery Learning, Contextual Teaching and Learning, and Number Head Together). The research employed a mixed-method approach with four stages of action research: planning, implementation, observation, and reflection. The subjects of the study were 24 fifth-grade students. The variables observed included teacher activity, student engagement, critical thinking skills, and learning outcomes. The results showed a significant improvement in all observed aspects. Teacher activity increased from a score of 16 to 24. Active student engagement rose from 21% to 92%. Students' critical thinking skills improved from 17% to 88%, meeting the criteria for active/very active. Learning outcomes also showed improvement across cognitive (17% to 92%), affective (21% to 96%), and psychomotor (17% to 96%) aspects. The application of the PBL DICONTOH model was proven effective in enhancing the quality of learning, critical thinking skills, and students' learning outcomes in ecosystem material. This model encourages active participation, conceptual understanding, and meaningful learning experiences.